The Effect of Chunks Teaching On Iraqi EFL Students’ Performance in Speaking (Journal of the College of Basic Education, 2022)
Speaking skill is the important of the other skills and it is considered as the core skill in language learning. The current study aims at investigating “the effect of chunks teaching on Iraq EFL students’ performance in speaking” A null hypothesis is adopted in the current study which indicates that there is no significant difference between the performance of students who are teaching chunks to develop their ability of that do not use.. The sample of the current study was 34 from the second stage / Information and libraries Department / College of Art. A ten weeks experiment was conducted on the experiment with pre and posttest. The experiment was started on 11 October and ended in 14th January, 2017. This study adopted (pretest- posttest). To ensure both (validity and reliability), the researcher submitted the initial test to the jury members. At the end of the experiment; the calculated results have been analyzed. So, teaching chunks is more effect than the traditional one in speaking. Finally, this study has put down conclusions, and some recommendations.